The effect of government public relations effectiveness of Bogor City government in disseminating information through TikTok social media (@pemkotbogor) - Kessya Rosa Augustine; Restiawan Permana; Yogaprasta Adi Nugraha (Priviet Social Sciences Journal, 2026)
The development of information technology has driven a transformation in public communication strategies, particularly through social media. Tiktok, as one of the short-form video-based platforms, as experienced significant growth in Indonesia, with over 150 million users recorded in 2024. This platform is no longer used solely for entertainment purposes but has also been adopted by various institutions, including government bodies, as an effective and real-time medium for disseminating information to the wider public. This study aims to determine the effectiveness of the public relations division of the Bogor City Government in disseminating information to the public through the TikTok social media account @pemkotbogor. This research uses a quantitative method with a survey approach to collect data from active TikTok users who follow the account. The study was conducted in the Bogor City area using purposive sampling, selecting respondents based on their active use of TikTok social media. The results indicate that the public relations activities through the TikTok account @pemkotbogor are effective in spreading information to the community, demonstrated by high levels of understanding, interaction, and message reach. In conclusion, the use of TikTok social media by the Bogor City Government can serve as an efficient public communication strategy in the digital era; however, continuous improvement in content quality and interactivity is needed to reach a wider audience.